Maternal Metabolic Health Parameters During Pregnancy in Relation to Early Childhood BMI Trajectories. Issue 3 (5th February 2018) - Montazeri, Parisa; Vrijheid, Martine; Martinez, David; Basterrechea, Mikel; Fernandez‐Somoano, Ana; Guxens, Monica; Iñiguez, Carmen; Lertxundi, Aitana; Murcia, Mario; Tardon, Adonina; Sunyer, Jordi; Valvi, Damaskini
Abstract : Objective: The objective of this study was to evaluate the associations between maternal metabolic parameters and early childhood BMI trajectories. Methods: Two thousand two hundred fifty‐one children born in Spain between 2004 and 2008 were analyzed. Five BMI z score trajectories from birth to age 4 years were identified by using latent class growth analysis. Multinomial regression assessed the associations between maternal metabolic parameters and offspring's BMI trajectories. Results: Children in the reference BMI trajectory had average size at birth followed by a slower BMI gain. Maternal prepregnancy obesity was associated with trajectories of accelerated BMI gain departing from either higher (relative risk ratio [RRR] = 1.77; 95% CI: 1.07‐2.91) or lower size at birth (RRR = 1.91; 95% CI: 1.17‐3.12). Gestational weight gain (GWG) above clinical guidelines was associated with a trajectory of higher birth size followed by accelerated BMI gain (RRR = 2.14; 95% CI: 1.53‐2.97). Maternal serum triglycerides were negatively associated with BMI trajectories departing from lower birth sizes. Gestational diabetes, maternal serum cholesterol, and C‐reactive protein were unrelated to children's BMI trajectories. Conclusions: Maternal prepregnancy obesity, GWG, and serum triglycerides are associated with longitudinal BMI trajectories in early childhood that may increase disease risk in later life. Health initiatives should promote healthy weight status before and during pregnancy to improve maternal and child health.